2018
DOI: 10.14434/pders.v37i2.25738
|View full text |Cite
|
Sign up to set email alerts
|

Building an Inclusive Post-Secondary Education Program for Young Adults with Intellectual Developmental Disability

Abstract: Since the reauthorization of The Higher Education Opportunity Act (HEOA) in 2008, postsecondary programs that include individuals with intellectual developmental disability have seen a phenomenal increase. In 2015, a National Coordinating Center along with 52 Transition and Postsecondary Programs for Students with Intellectual Disabilities (TPSID) were created and funded through the U.S. Department of Education’s Office of Postsecondary Education. Currently, 267 programs are listed on the National Coordinating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 10 publications
0
1
0
Order By: Relevance
“…The Bureau of Labor Statistics (2022) reports 19.1% of people with disabilities were employed compared to 63.7% of their peers without a disability. Research has shown that long-term career outcomes for individuals with disabilities can drop to a rate as long as 17.2% (Baker, Lowrey, & Wennerlind, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The Bureau of Labor Statistics (2022) reports 19.1% of people with disabilities were employed compared to 63.7% of their peers without a disability. Research has shown that long-term career outcomes for individuals with disabilities can drop to a rate as long as 17.2% (Baker, Lowrey, & Wennerlind, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The Bureau of Labor Statistics (2022) reports 19.1% of people with disabilities were employed compared to 63.7% of their peers without a disability. Research has shown that long-term career outcomes for individuals with disabilities can drop to a rate as long as 17.2% (Baker, Lowrey, & Wennerlind, 2018). Research on evidence-based practices indicated that early employment experiences, supported internships, and collaboration are effective in preparing and supporting IWDs for their transition to employment (Bellman, Burgstahler, & Ladner, 2014;Lee & Carter, 2012).…”
mentioning
confidence: 99%